2022
DOI: 10.3389/fnagi.2022.821915
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transcranial Direct Current Stimulation Dosage and Associated Therapy on Motor Recovery Post-stroke: A Systematic Review and Meta-Analysis

Abstract: Purpose(1) To determine the impact of transcranial direct current stimulation (tDCS) applied alone or combined with other therapies on the recovery of motor function after stroke and (2) To determine tDCS dosage effect.MethodsRandomized controlled trials comparing the effects of tDCS with sham, using the Barthel Index (BI), the upper and lower extremity Fugl–Meyer Assessment (FMA), and the Modified Ashworth Scale (MAS), were retrieved from PubMed, Medline (EBSCO), and Cumulative Index to Nursing and Allied Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Consistently, the recent literature shows that in humans, tDCS improved long-term motor recovery when applied in addition to established rehabilitation regimes but not alone. [56][57][58] In this context, it would be interesting to investigate tDCS combined with physical exercise or an enriched environment, which was not addressed in this study. However, both enhanced recovery of function and modulation of inflammation after stroke have repeatedly been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the recent literature shows that in humans, tDCS improved long-term motor recovery when applied in addition to established rehabilitation regimes but not alone. [56][57][58] In this context, it would be interesting to investigate tDCS combined with physical exercise or an enriched environment, which was not addressed in this study. However, both enhanced recovery of function and modulation of inflammation after stroke have repeatedly been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that transcranial direct current stimulation was more effective in patients with subacute stroke than in those with acute and chronic stroke experiencing upper limb dysfunction. However, three studies reached different conclusions, among which two 8,9 showed a more effective effect of transcranial direct current stimulation in patients with chronic stroke, while one 11 showed a more effective effect in those with acute stroke. Notably, transcranial direct current stimulation can interfere with or even disrupt spontaneous recovery in the acute phase, emphasizing the need for caution when interpreting these results.…”
Section: Discussionmentioning
confidence: 97%
“…10 Previous systematic reviews and meta-analyses investigating the effects of transcranial direct current stimulation in combination with other treatments and at different doses have not yielded conclusive results. [11][12][13] Additionally, guidelines for selecting transcranial direct current stimulation types or stimulus parameters are currently unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…tDCS can also be applied with various set‐ups including anodal stimulation (a‐tDCS), cathodal stimulation (c‐tDCS), and dual stimulation (d‐tDCS; the most common) (List et al., 2015 ; Vines et al., 2008 ). Recent studies have shown inconclusive results when applying tDCS for motor skill improvement using scales such as the FMA (Chow et al., 2022 ); however, considering the ICF division, that same study and other systematic reviews with meta‐analyses have shown that all types of tDCS stimulation are effective, but it appears that ctDCS may have greater effectiveness in improving activities of daily living and independence (Chow et al., 2022 ; Elsner et al., 2020 , 2017 ). The atDCS approach appears to show more significant improvements in motor ability (Xue et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%